Not Only One But Many: How is the Islamic Educational Contest Shaping Indonesian Muslim Profiles? - Amin, Khairul (Muslim Education Review, 2024)
Through the historical lens, we can see that the development of religious group diversity in certain religions is real and inevitable, including in Islam. Various factors can be put forward to explain this, but of all possible explanations, education surely has the crucial role. In the Indonesian context, the development of Islamic education has generated multi-faces of Muslims. Since the first educational reform in the early twentieth century, Islamic education has not only been a response to the colonial government’s ethische politiek policy, but has also become a crucial factor in the making of Indonesian Muslim faces. This article attempts to explore how the Islamic educational contest generally has shaped the Indonesian Muslim profile, at least since the early twentieth century until nowadays, with heuristic and sociological approaches in the frame of process philosophy, specifically on development of education, rather than political and ideological debate. The aim of this article is to illustrate the extent to which educational developments and contestations among Islamic groups have general significance for the making of Indonesian Muslim profiles. This article found that: (1) educational contestation has a significant role in the making of multi-faces of Indonesian Muslims; (2) the diversity of Muslim profiles has steadily increased since educational reform and contestation took place; and (3) educational contestation occurs in a very dynamic way that involves not only ideological indoctrination, but also educational innovation and creative adaptation.